IELTS graduation : - Short, Jane (Macmillan, 2007)
IELTS graduation teacher's book offers assistance to experienced techers who are new to the IELTS exam. It provides all the information required to guide students through the demands of Acedemic English that they are likely to encouter, both in the exam and at university.